2007
DOI: 10.1093/wber/lhm008
|View full text |Cite
|
Sign up to set email alerts
|

Brain Drain in Developing Countries

Abstract: An original data set on international migration by educational attainment for 1990 and 2000 is used to analyze the determinants of brain drain from developing countries. The analysis starts with a simple decomposition of the brain drain in two multiplicative components, the degree of openness of sending countries (measured by the average emigration rate) and the schooling gap (measured by the education level of emigrants compared with natives). Regression models are used to identify the determinants of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
181
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(209 citation statements)
references
References 19 publications
6
181
2
5
Order By: Relevance
“…This matches the interpretation that those individuals who most likely have better job opportunities due to their advanced education are more likely to look for these opportunities in a location other than their original place (see also Docquier et al 2007;Beine et al 2008). Given our sampling strategy, which mostly captures rural-to-urban migration, this finding might be more pronounced than in studies examining urban-to-urban or rural-to-rural migration.…”
supporting
confidence: 71%
“…This matches the interpretation that those individuals who most likely have better job opportunities due to their advanced education are more likely to look for these opportunities in a location other than their original place (see also Docquier et al 2007;Beine et al 2008). Given our sampling strategy, which mostly captures rural-to-urban migration, this finding might be more pronounced than in studies examining urban-to-urban or rural-to-rural migration.…”
supporting
confidence: 71%
“…Bhagwati and Hamada, 1974;Bhagawati and Wilson, 1989;Wickramasekara, 2002;Commander et al, 2004;Schiff, 2005;Docquier et al, 2007) with respect to losses and benefits for the donor country, it is difficult to find research on the determinants behind the migrant's intentions and perception on choosing a foreign posting as a career option. Thus, this study aimed at investigating the determinants that facilitate Sri Lankan university students' and graduates' persuasion towards seeking overseas jobs and to identify whether the actual behaviour is facilitated by the perceived behaviour toward overseas jobs.…”
Section: Conceptual Framework Of the Studymentioning
confidence: 99%
“…Recently, a few recent contributions take advantage of new databases in international migration by education level to investigate the determinants of the brain drain and the skill composition of emigration flows. Docquier, Lohest and Marfouk (2007) showed that the brain drain increases with political instability and the degree of fractionalization, and decreases with the level of development at origin. Grogger and Hanson (2008) found that a simple model of income maximization can account for positive selection (higher emigration rates for the skilled) and positive sorting (positive effect of wage differentials on the share of skilled in bilateral migration).…”
Section: Introductionmentioning
confidence: 99%